Answer:
A(y=3) B(y = -2) C(y= 4)
A' (y = 3) B(y= -2) C(y= 4)
Step-by-step explanation:
Answer:
7
Step-by-step explanation:
Do addition first, so 30 plus 2, and then subtract, 32 minus 25. It is seven.
Answer:
When x = -2, y = 3
When x = -1, y = 0
When x = 0, y = -3
When x = 1, y = -6
Step-by-step explanation:
Given:
y = -3x - 3
Fill in the table using the following value for x
When x = -2
y = -3x - 3
y = -3(-2) - 3
y = 6 - 3
y = 3
When x = -2, y = 3
When x = -1
y = -3x - 3
y = -3(-1) - 3
y = 3 - 3
y = 0
When x = -1, y = 0
When x = 0
y = -3x - 3
y = -3(0) - 3
y = 0 - 3
y = -3
When x = 0, y = -3
When x = 1
y = -3x - 3
y = -3(1) - 3
y = -3 - 3
y = -6
When x = 1, y = -6
I believe it’s 80 hope it helps
Answer:
B. l = (S - πr^2) / πr
Step-by-step explanation:
S = πrl + πr^2 solve for l
πrl = S - πr^2
l = (S - πr^2) / πr
Answer is B. l = (S - πr^2) / πr